Immunobiological status of the organism of young pigs during their triphasic period cultivation and actions of corrective factors - N. Yu. Krempa; O. V. Kozenko; B. V. Gutyj; I. V. Dvylyuk; N. V. Magrelo; H. V. Sus; U. M. Vus; T. V. Martyshuk; V. V. Voroniak; A. O. Vysotskyi; O. O. Dashkovskyi (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The problem of the impact and consequences of technological stress is accompanied by several reactions that do not always have a positive effect on the animal's body. The work aimed to investigate the dynamics of indicators of the immunobiological status of piglets during their three-phase rearing and the use of immunostimulating agents Globigen® Pig Doser and Globigen® Jump Start. Parallel studies were conducted based on the private farm “Meat Resources” LLC of the Lviv region of the Starosambir district, which practices three-phase pig breeding. The experiment involved 36 analog piglets and hybrids of Landrace and Great White breeds, which were formed into 3 groups of 12 animals each. Piglets of the control group were fed the standard ration provided by the technology. During the first three days of life, newborn piglets of the first experimental group were given 2 ml/gal of liquid Globigen®Pig Doser. The piglets of the second experimental group were given a powdered dry product Globigen®Jump Start, which was added to the main diet at 0.2 % per ton of feed. It was established that the use of means with an immunostimulating effect was accompanied by a decrease in the content of Ig M in the blood samples of experimental groups of piglets. Thus, in the blood serum of 30-day-old piglets under the influence of Globigen® Pig Doser with a high level of probability (Р < 0.02), a decrease in the content of this class of antibodies was found to the level of 1.59 mg/ml, and under the influence of Globigen® Jump Start the content in the blood serum of 60-day-old piglets, having reached the lowest value, was 2.08 mg/ml. The positive effect of immunostimulating agents, which was characterized by an increase in the amount of Ig G, was found in experimental groups of pigs at the age of 60 days: 17.10 mg/ml for the effects of Globigen® Pig Doser and 17.08 mg/ml for the impact of Globigen® Jump Start. The highest content of Ig A with high probability (P < 0.001) was found in blood samples of animals that were given Globigen® Jump Start – 3.45 mg/ml and 3.86 mg/ml under the influence of Globigen® Pig Doser. The practicality and effectiveness of the use of means with immunostimulating properties, the main active ingredient of which is the immunoglobulin of a chicken egg, is explained by the ability to influence the pathogenesis of diseases of the gastrointestinal tract, which arise as a result of weakening the resistance of the animal body under the influence of a large number of technological stresses. Research data prove that the specificity of the action of Ig Y has a positive effect on the preservation of the integrity of the villi of the intestinal mucosa, which is reflected by the strengthening of its protective and barrier function, which in general contributes to the increase in the percentage of animal survival: using Globigen®Pig Doser 80.0 % and 86.7 % using Globigen®Jump Start. Based on such results, it can be asserted that the use of Globigen® Pig Doser and Globigen® Jump Start for three-phase pig farming is scientifically justified and economically feasible.